Evidence for Subsoil Specialization in Arbuscular Mycorrhizal Fungi - Sosa-Hernández, Moisés A.; Roy, Julien; Hempel, Stefan; Rillig, Matthias C. (Frontiers in Ecology and Evolution, 2018)
Arbuscular mycorrhizal (AM) fungal communities are now known to vary with depth in arable land. Here we use two previously published high-throughput Illumina sequencing data sets, and compare a 52 year long chronosequence of recultivated agriculture fields after a topsoil and subsoil mixing event, with a set of undisturbed topsoil and subsoil samples from a similar field. We show that AM fungal taxa identified as subsoil indicators are exclusively present in early stages of the chronosequence, whereas topsoil indicator taxa can be found across the chronosequence. Also, community-level similarities from the chronosequence fields to the subsoil decrease with time. Our results provide evidence of ecological specialization of certain AM fungal taxa to deep soil layers.